The prevalence of oral manifestations of Iron Deficiency Anemia in patients attending to College of Dentistry - Jaber, Hanaa Khazaal; Husseien, Hala A.; Al Qudsi, Ghaydaa Hashim (Journal of Pakistan Association of Dermatologists, 2023)
Objective Iron deficiency anemia (IDF) presented with specific oral features and a specific blood profiles. This study aimed to document the presence, severity and prevalence of the oral features of IDA in patients attending College of Dentistry. Methods Totally, 180 cases enrolled. Past medical and surgical plus clinical examination done for each participant. Any features of anemia, oral mucosal manifestations were recorded. The distinguish of the oral mucosal forms were clinically depend on lesions basis. Results The findings showed that the prevalence at different hemoglobin (Hb) levels in the IDA group included fissured tongue (32.3%), atrophic glossitis (AG) (24%), recurrent aphthous ulcer (RAU) (15%) pallor(16%), oral candidiasis (5%), burning sensation (2.2%), oral pigmentation (2.2%), angular cheilitis (1.1%), and periodontitis (0.6%). Conclusion Through this research, information was added to us about the effects of anemia on the oral cavity and the etiology of lesions and through it we can reach the correct diagnosis and treatment as early as possible and thus reduce the harmful adverse events of anemia.